2016
DOI: 10.1002/tox.22368
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid compounds from the red marine alga Alsidium corallinum protect against potassium bromate‐induced nephrotoxicity in adult mice

Abstract: Potassium bromate (KBrO ), an environmental pollutant, is a well-known human carcinogen and a potent nephrotoxic agent. Currently, natural products have built a well-recognized role in the management of many diseases induced by pollutants. As potent natural sources of bioactive compounds, marine algae have been demonstrated to be rich in novel secondary metabolites with a broad range of biological functions. In this study, adults male mice were orally treated for 15 days with KBrO (0.5 g/L) associated or not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 59 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…In the present study, our results showed that TMX treatment resulted in a significant DNA reduction as well as massive DNA fragmentations with a subsequent formation of a DNA smear on agarose gel, thus confirming TMX‐induced necrosis and apoptosis as indicated by histological observations. Following pesticide toxicity, excessive ROS formation might induce changes or losses of nucleotide bases in the DNA, therefore causing mutagenic lesions . It can be assumed that TMX or its main metabolite(s) might act by disrupting the balance between lesion inductions from radical processes and repair systems, giving ROS over production leading to DNA breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our results showed that TMX treatment resulted in a significant DNA reduction as well as massive DNA fragmentations with a subsequent formation of a DNA smear on agarose gel, thus confirming TMX‐induced necrosis and apoptosis as indicated by histological observations. Following pesticide toxicity, excessive ROS formation might induce changes or losses of nucleotide bases in the DNA, therefore causing mutagenic lesions . It can be assumed that TMX or its main metabolite(s) might act by disrupting the balance between lesion inductions from radical processes and repair systems, giving ROS over production leading to DNA breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Saad et al [173] demonstrated a flavonoid-enriched extract from Alsidium corallinum containing flavonoids such as luteolin 5,7,3 ,4 tetramethyl ether, quercetin 3,7 dimethylether 4 sulfate, and catechin trimethyl ether, which can be useful tools against the kidney dysfunction provoked by potassium bromate; this assay was done in mice.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Indeed, many metabolite studies on algae report only amounts of "total flavonoids" measured using general assays. Nevertheless, there are some reports detailing specific flavonoid structures in algal preparations, including compounds such as chalcones, flavones, flavonols, isoflavonoids, and proanthocyanidins (Klejdus et al, 2010;Goiris et al, 2014;El Shoubaky et al, 2016;Agregán et al, 2017;Ben Saad et al, 2017). Although the concentrations of flavonoid compounds reported in most examples are extremely low compared with those commonly found in land plants (ng gDW −1 amounts compared with mg gDW −1 ), these reports mean that the presence of a biosynthetic pathway to flavonoids in algae cannot be ruled out.…”
mentioning
confidence: 99%